The cellulose structural transformation for higher enzymatic hydrolysis by ionic liquids and predicting their solvating capabilities. (1st February 2016) - Raj, Tirath; Kapoor, Manali; Semwal, Surbhi; Sadula, Sunitha; Pandey, Vibhav; Gupta, Ravi P.; Kumar, Ravindra; Tuli, Deepak K.; Das, B.P.
Abstract: Lignocellulosic material (LCM) is promising alternative resource for sustainable energy production such as ethanol and butanol and biohydrogen. Cellulose is an abundant renewable polymer of LCM found in plant cell walls (30–50%). The high crystallinity of cellulose makes it recalcitrant to hydrolysis into its individual sugar subunits for biofuels production. Moreover, ionic liquids are considered as green solvents and have been used for biomass solubilization. The present work describes three properties: Kamlet–Taft (K–T) parameters, viscosity and surface tension of five imidazolium-based ionic liquids (ILs); namely [C2 mim][OAc], [C4 mim][OAc], [C2 mim][Cl], [C4 mim][Cl] and [C4 mims][BF4 ], and their efficiency in the cellulose structural transformation for improved enzymatic glucose recovery. Crystalline cellulose was treated with ILs at two different temperatures, i.e. 100 and 130 °C for 5 and 2 h, respectively, with 10% solid loading followed by enzymatic saccharification using 10 and 20 FPU/g substrate of commercial cellulases. ILs treatment of crystalline cellulose significantly reduces the crystallinity, which resulted in a very sharp increase of sugar yields after enzymatic saccharification. Cellulose treated for 130 °C/2 h resulted in better glucose yields as compared to 100 °C/5 h. ILs comprising acetate anion resulted in highest glucose yields and chloride based ILs performed moderately, whereas BF4 − based IL was ineffective in transforming the cellulose structure. In order to decipher the possible reasons of varying efficiency of these ILs, the K–T parameters; hydrogen bond acidity (α), hydrogen bond basicity (β), solvent polarizability (π ∗ ), kinematic viscosity (η) and surface tension (σ) were calculated for 100 and 130 °C. These results show that, among all the properties of ILs, hydrogen bond basicity (β) is relatively more important than kinematic viscosity and surface tension for impacting the structural transformation and subsequent enzymatic hydrolysis. [C2 mim][OAc] with high β value (1.32) and lower viscosity (4.4 cSt/s) and surface tension (30.3 mN/m) was found to be most efficient in cellulose transformation resulting in higher glucose yields (89.8%) upon saccharification. Effect of size of cation and anion of ILs and properties of regenerated cellulose is also examined by PXRD and FT-IR to further support the findings. Graphical abstract: Highlights: Treatment efficiencies of five ionic liquids are studied. ILs with β > 0.72 resulted >55% glucose yield after 24 h. Viscosity and surface tension of ILs have a negative correlation with glucose yields. [C2 mim][OAc] with high β, smaller anion and shorter alkyl chain gave highest glucose yields with maximum reduction in CrI. [C4 mim][BF4 ] was not at all effective in improving the glucose yields.